2021
DOI: 10.1055/a-1293-6965
|View full text |Cite
|
Sign up to set email alerts
|

Is jumbo biopsy forceps comparable to cold snare for diminutive colorectal polyps? – a meta-analysis

Abstract: Background and study aims Diminutive colorectal polyps are increasingly being detected and it is not clear whether jumbo biopsy forceps (JBF) has comparable efficacy to that of cold snare polypectomy (CSP) for management of these lesions. Methods An electronic literature search was performed for studies comparing resection rates of JBF and CSP for diminutive polyps (≤ 5 mm). The primary outcome was incomplete resection rate (IRR). Secondary outcomes included failure of tissue retrieval and complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The ESGE and US MultiSociety Task Force gui delines recommend CSP as the firstline method for removing diminutive (≤5 mm) and small (6-9 mm) polyps, and they recommend against the use of CFP for these lesions due to the high rates of IPR, ac cepting its use for polyps ≤2-3 mm where CSP is technically difficult (9,10) . For these lesions, the US Mul tiSociety Task Force guidelines recommend the use of jumbo or largecapacity forceps (10) .A metaanalysis comparing the use of jumbo forceps vs CSP for remo ving diminutive polyps showed an IPR rate of 10.2% vs 7.2%, respectively, without statistically significant difference between them (25) .…”
Section: Discussionmentioning
confidence: 99%
“…The ESGE and US MultiSociety Task Force gui delines recommend CSP as the firstline method for removing diminutive (≤5 mm) and small (6-9 mm) polyps, and they recommend against the use of CFP for these lesions due to the high rates of IPR, ac cepting its use for polyps ≤2-3 mm where CSP is technically difficult (9,10) . For these lesions, the US Mul tiSociety Task Force guidelines recommend the use of jumbo or largecapacity forceps (10) .A metaanalysis comparing the use of jumbo forceps vs CSP for remo ving diminutive polyps showed an IPR rate of 10.2% vs 7.2%, respectively, without statistically significant difference between them (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Most new studies have assessed the use of jumbo biopsy forceps in comparison to CSP. A meta-analysis by Srinivasan et al [39] showed that the incomplete resection rate (IRR) for jumbo biopsy forceps was arithmetically higher compared with CSP, but this did not reach statistical significance. This meta-analysis was most likely underpowered and only included four studies, with one of these constituting > 50 % of the total of 407 patients.…”
Section: Resection Of Diminutive Polyps (≤ 5 Mm)mentioning
confidence: 99%